Analysis of factors for non-disclosure of information by doctor-investigators in clinical trials in Malaysia - Yusof, Yuhanif; Abdullah, Nor Anita; Megat Latif, Hairuddin; Md Desa, Md Rejab; Che Ngah, Anisah (Asia Pacific Institute of Advanced Research (APIAR), 2017)
In clinical trials, the need to obtain patient’s consent by way of informed consent has been mandatorily imposed as a way to protect the patient as subject.Unfortunately, many studies have shown that the doctor-investigators had failed to disclose full information to patients. Hence, the aim of this paper is to examine the factors for non-disclosure of information by doctor-investigator and provide potential solutions to the problem.This study employed a mixed-method data collection that is library research and interview.A qualitative methodology and analysis were used in an open-ended, face-to-face interviews with 12 patients recruited to participate in a trial to investigate drug for chemotherapy and schizophrenia. This study reveals that doctor-investigators fail to disclose information due to the absence of monitoring by the ethics committees and that the Good Clinical Practice Training Curriculum (GCPTC) is too basic and almost introductory and the attitude of the patient that put high hopes on doctor investigators.Hence, random monitoring by the ethics committees and monitoring using video tape during the informed consent process are recommended.In addition, GCPTC needs to be improvised and further enhanced by inserting topic on the differences of objective between medical treatment and clinical trials and topic on infamous conduct according to Code of Profesional Conduct 1987 (CPC).In addition, a framework model in respect of information disclosure is also proposed by incorporating several new clauses in the CPC equivalent to the requirements of internationally recognized rights of patient as subject.